Problem-Based Learning and Mind Mapping: Boosting Creativity in Architecture Education - Eko Nursanty; Rahmawaty Abu Hasan; Thazin Htet (SARGA: Journal of Architecture and Urbanism, 2022)
This paper focuses on unlocking the creative potential of architecture students through an exploration of the Four C model of creativity. This model extends the traditional understanding of creativity and offers a comprehensive framework for fostering innovation in architecture. It introduces "mini-c" and "Pro-c" dimensions, highlighting creativity within the learning process and the attainment of professional expertise. Architecture demands a blend of technical skills and artistic expression for effective communication of ideas. However, nurturing creative thinking among architecture students faces challenges, including fear of experimentation and traditional teaching methods. To address these obstacles, the paper suggests integrating problem-based learning (PBL) and mind mapping techniques. PBL encourages collaboration and critical thinking, while mind mapping stimulates visual and associative thinking, aiding idea generation and organization. Additionally, the role of technology in architecture education is explored, emphasizing the benefits of mixed learning environments that enhance collaboration and creativity. Embracing technology readiness equips students with tools to tackle real-world challenges and create innovative designs. In conclusion, this paper underscores the importance of creative thinking in architectural design and its implications for the discipline's future. By adopting the Four C model, implementing PBL with mind mapping, and leveraging technology, educators can revolutionize architecture education, nurturing a new generation of architects prepared to shape the evolving world with imaginative and visionary designs.